2020
DOI: 10.1111/ijcp.13816
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between “nomophobia” and material addiction “cigarette” and factors affecting them

Abstract: Since technological devices used for communication affect communication between people, nomophobia is a disorder of a new age. In this study, we discuss the relationship between nomophobia and smoking addiction and the factors affecting them. The Demographic Information Form and Nomophobia Scale (NMP‐Q), ıf they were smoking we applied The Fagerström Test for Nicotine Dependence (FTND) Scales were directed among students (n = 641) at Süleyman Demirel University studying Medicine, Dental, Nursing and Physiother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Studies have indicated that nomophobia is more prevalent among women [15] and young people, especially those aged <24 years [7,8,16], which is consistent with the profile of nursing students [17].…”
Section: Introductionsupporting
confidence: 66%
“…Studies have indicated that nomophobia is more prevalent among women [15] and young people, especially those aged <24 years [7,8,16], which is consistent with the profile of nursing students [17].…”
Section: Introductionsupporting
confidence: 66%
“…While some studies among university students in Oman and Turkey revealed no significant difference between nomophobia and smoking habits, this may be due to a small sample size or a lack of smoker participants. 21 , 41 Similarly, Dib et al found in a study among the Lebanese population that nomophobia and smoking were unrelated. However, a significant correlation was reported between nomophobia and waterpipes because of the length of time spent using a hookah.…”
Section: Discussionmentioning
confidence: 97%
“…43 (28-48); one to two hours: 43(38)(39)(40)(41)(42)(43)(44)(45)(46)(47); three to four hours: 44; five hours or more: 54 (42-68); (p <0.001)).…”
mentioning
confidence: 97%
“…We found a negative association between smartphone addiction and the use of substances with addictive potential. While examining the available literature, most research conducted on young individuals (both university and medical students) discovered no correlation [ 24 , 38 , 39 , 40 , 41 ]. On the other hand, Liu et al observed a positive association among Chinese medical students, and Dey et al observed a negative association among Swiss young men [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%